Effects of Interval Training Under Hypoxia on Hematological Parameters, Hemodynamic Function, and Endurance Exercise Performance in Amateur Female Runners in Korea - Park, Hun-Young; Jung, Won-Sang; Kim, Sung-Woo; Kim, Jisu; Lim, Kiwon (Frontiers in Physiology, 2022)
Interval training under hypoxia (IHT) is commonly used to enhance endurance exercise performance because of its effect on non-hematological parameters. However, it is important to examine its effects on hematological parameters, including immune function, to assess its influence on health and conditioning. This study aimed to evaluate the effects of IHT for 6-week on hematological parameters, hemodynamic function, and endurance exercise performance in amateur Korean female runners. Twenty healthy amateur Korean female runners (age: 24.85 ± 3.84 years) were equally assigned to normoxic training group (NTG) for interval training under normoxia (760 mmHg) and hypoxic training group (HTG) for interval training under hypobaric hypoxia (526 mmHg, 3000 m simulated altitude) according to their body composition and endurance exercise performance. All participants performed 120-min of training sessions, consisting of 20-min of warm-up, 60-min of interval training, and 20-min of cool-down. The training program was performed 3-day per week for 6-week. Warm-up and cool-down were performed for 20-min at 60% maximal heart rate (HRmax). The interval training sessions comprised 10 repetitions of interval exercise (5-min of exercise corresponding to 90–100% HRmax and 1-min of rest) on a treadmill. All participants underwent measurements of hematological parameters, hemodynamic function, and endurance exercise performance before and after training. Both groups showed a significant increase in erythropoietin (EPO) level and a decrease in monocyte abundance, with EPO showing a greater increase in HTG than in NTG. B cell abundance significantly increased in NTG; hematocrit and neutrophil counts significantly increased, and lymphocyte counts significantly decreased in HTG. The HTG showed a significant improvement in oxygen uptake, stroke volume index, and end-diastolic volume index compared to the NTG. In addition, both groups showed significant improvements in heart rate, end-systolic volume index, and cardiac output index. The maximal oxygen uptake and 3000 m time trial record were significantly improved in both groups, and the HTG showed a tendency to improve more than the NTG. In conclusion, IHT was effective in enhancing endurance exercise performance through improved hemodynamic function. Furthermore, hematological parameters of immune function showed a normal range before and after training and were not negatively affected